Multisite implementation of trained volunteer doula support for disadvantaged childbearing women: a mixed-methods evaluation - Helen Spiby; Josephine M Green; Zoe Darwin; Helen Willmot; David Knox; Jenny McLeish; Murray Smith (National Institute for Health Research, 2015)
Background: The research examined an innovative volunteer doula service, established in one city and rolled out to four other sites. The initiative offers support to disadvantaged women with the aim of enhancing well-being and improving the uptake of health services. Aims: The project addressed four broad questions: implications for the NHS; health and psychosocial impacts for women; impacts on doulas; and the processes of implementing and sustaining a volunteer doula service for disadvantaged childbearing women. Design: A mixed-methods study using interviews, focus groups and questionnaires to obtain primary data from a range of stakeholders. Existing data sets were used to examine clinical and public health outcomes and contributed to a cost-consequence analysis. A realistic evaluation perspective supported investigation of a complex intervention in its real-world context. Outcomes: We assessed impacts, perceptions and experiences of women, doulas, midwives and heads of midwifery. Clinical and public health outcomes included epidural use, rates of caesarean section, low birthweight, admission to neonatal unit, smoking and breastfeeding. The costs of running a doula service and cost implications for the NHS were calculated. Data sources: Data sources included the service database at the original site; available outcomes were compared against those in reference data sets. Women completed questionnaires and a small number participated in focus groups. Doulas contributed information through focus groups, postal questionnaires and telephone interviews. Staff, commissioners and local champions of doula services provided information through interviews and focus groups. Midwives and heads of midwifery took part in focus groups and telephone interviews respectively. Results: Although doula-supported women in the original site used fewer epidurals and generally required fewer caesarean sections than women in reference groups, these differences were not statistically significant. The utility of comparisons is constrained by the absence of parity information from comparison data. For outcomes with a low incidence, data were pooled across years; this included comparisons for low birthweight and admission to neonatal units where no significant differences were observed. Reductions in rates of smoking at birth were not consistently statistically significantly different from available comparators. More doula-supported women initiated breastfeeding and were continuing at 6 weeks. Initiation rates were significantly higher for most years than in reference groups and significantly higher for continued breastfeeding for all years. The majority of women who accepted doula support valued it highly for its continuity and doulas' availability and flexibility, being listened to by someone who was non-judgemental and having fears allayed, together with building self-esteem. Women also appreciated volunteer doulas for the knowledgeable companionship, relief of isolation and help with accessing services. Nearly all doulas enjoyed the role and felt well prepared by their training and the majority felt well supported. Midwifery staff appreciated volunteer doulas for their commitment and support to women. Doula services' challenges in implementing and sustaining their services included funding, balancing referrals and volunteer availability, and relationships with other organisations. The costs of providing a doula service varied considerably, with some costs absorbed by host organisations. Some improved clinical outcomes point to potential cost benefits to the NHS although these were less than the per birth costs of the service in the original site. Conclusions: This is the largest independent evaluation of volunteer doula support in the UK. Limitations include lower than optimal questionnaire response rates and the relatively small sample size available for outcome measurement. Our findings of positive psychosocial impacts reflect those reported among women in other settings, where women may not have access to midwifery support. Significant improvements in maintaining breastfeeding were particularly striking. Volunteer doulas were highly regarded by women and doula support was accepted by NHS midwives. Doulas enjoyed the role and reported positive impacts for various areas of their lives. Funding was a continuing challenge for doula services. Funding: The National Institute for Health Research Health Services and Delivery Research programme.